Consumer Perceptions of Sustainable Use of Digital Wallets: A Monitoring Study of Users in the DANA Application - Simorangkir, Andriy Hasiholan; Fourqoniah, Finnah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the level of consumer satisfaction with the DANA application as a digital wallet service provider, using five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. This study is a quantitative study conducted through a survey method, using a non-probability sampling technique. Data were collected using questionnaires and data triangulation through interviews. Data analysis includes the calculation of the arithmetic mean, SERVQUAL analysis, and importance performance analysis. The survey was conducted on 91 people who are active users of the DANA Application digital wallet. The results of the study showed that the performance of the DANA application in serving consumers was considered good with an average total score of 4.09. Meanwhile, consumer expectations of service quality are in the very high category, with an average score of 4.7. The total average difference (GAP) of -0.61 indicates that DANA's service quality is perceived as quite ordinary by consumers. In addition, the average total performance-importance value of 87% shows that the level of consumer satisfaction with service quality based on the five quality dimensions is not optimal